Transcriptional Regulation and Characteristics of a Novel N-Acetylmuramoyl-l-Alanine Amidase Gene Involved in Bacillus thuringiensis Mother Cell Lysis - Yang, Jingni (American Society for Microbiology, 2013)
In Bacillus thuringiensis, a novel N-acetylmuramoyl-l-alanine amidase gene (named cwlB) was detected, and the CwlB protein was purified and characterized. Reverse transcription-PCR (RT-PCR) results indicated that cwlB and an upstream gene (named cwlA) formed one transcriptional unit. 5′ rapid amplification of cDNA ends (5′-RACE)-PCR and transcriptional fusions with the lacZ gene indicated that transcription of the operon was directed by a promoter, P(cwlA), which is located upstream from the cwlA gene and that the transcription start site is a single 5′-end nucleotide residue T located 25 nucleotides (bp) upstream from the cwlA translational start codon. Moreover, the activity of P(cwlA) was controlled by σ(K). Morphological analysis suggested that the mutation of cwlB could delay spore release compared to the timing of spore release in the wild-type strain. Western blot assay demonstrated that purified CwlB bound to the B. thuringiensis cell wall. Observations with laser confocal microscopy and a green fluorescent protein-based reporter system demonstrated that the CwlB protein localizes to the cell envelope. All results suggest that the CwlB protein is involved in mother cell lysis in B. thuringiensis.